Meningkatkan Hasil Belajar Atletik Lari Jarak Pendek Melalui Bermain Dengan Media Bilah Bambu Bagi Siswa Kelas IV SD Negeri Gerintuk - Sukarman Sukarman (Universitas Pendidikan Mandalika, 2022)
This study aims to improve the learning outcomes of short-distance running athletics through playing with bamboo blades for fourth graders at SD Negeri Gerintuk. This research uses classroom action research method with 15 students as research subjects. The technique of collecting data in this research is to use observation sheets and documentation. The data analysis technique used descriptive analysis. The results showed that playing with bamboo slats has been able to improve the learning outcomes of sprint athletics for fourth graders at SD Negeri Gerintuk. Based on the observation data, there was an increase, the results of the evaluation of the basic motion of short distance running with an average value in the pre-cycle of 66.7, in the first cycle to 72.8, and in the second cycle it increased to 82. An increase also occurred in the percentage of students' completeness from pre-cycle, namely students who completed only 5 students (33.3%), in the first cycle there was an increase to 9 students (60%), then in the second cycle increased to 13 students (86.7%).